2004
DOI: 10.1080/00039420400005075
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the precaecal and faecal digestibility of lactulose and inulin and their influence on nutrient digestibility and microbial characteristics

Abstract: This study was conducted to determine the pre-caecal and faecal digestibility of lactulose and inulin and the influence of these substances on nutrient digestibility and microbial characteristics. In metabolic trials three of six male growing pigs (German Landrace x Pietrain) were fitted with an ileo-rectal anastomosis (IRA) in end-to-end technique with preserved ileo-caeco-colic valve. The metabolic trials were conducted from day 21-63 after surgery. The remaining pigs were used as intact partners (IN) for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
23
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 25 publications
5
23
2
Order By: Relevance
“…Previously, in nonchallenged piglets fed lactulose, an improvement in the lactobacillus/enterobacterium ratio and increased butyrate levels were also detected (17). However, other authors have not reported a prebiotic effect for lactulose in the colon when including 1.5% in the diet of growing pigs (35). In that work, the authors also reported a high prececal digestion of lactulose that could be related to the fact that they were working with growing pigs.…”
Section: Discussionmentioning
confidence: 56%
“…Previously, in nonchallenged piglets fed lactulose, an improvement in the lactobacillus/enterobacterium ratio and increased butyrate levels were also detected (17). However, other authors have not reported a prebiotic effect for lactulose in the colon when including 1.5% in the diet of growing pigs (35). In that work, the authors also reported a high prececal digestion of lactulose that could be related to the fact that they were working with growing pigs.…”
Section: Discussionmentioning
confidence: 56%
“…Although a higher lactulose concentration in the ileum than in the jejunum might be a reason for the effect on villus heights only in the ileum. In a study with pigs from Kamphues et al (2003) and Branner et al (2004) higher lactulose concentrations were measured at the end of the small intestine than in the jejunum. Lactulose concentration in chyme of calves deserves further study.…”
Section: Discussionmentioning
confidence: 95%
“…Differences between effects of both prebiotic substances or different gut segments may be due to fermentation properties of the substances themselves (Branner et al, 2004). In addition, the density and composition of calf intestinal flora also vary greatly within the gut with decreasing anaerobic bacteria counts and a shift toward bifidobacteria from the rumen to the colon (Collado and Sanz, 2007).…”
Section: Discussionmentioning
confidence: 99%